Ecsiccatae of the Herbarium Florae Rossica of the historical herbarium of Uman College of Agriculture and Horticulture - Мамчур, Т. В.; Кравець, Т. О.; Чорна, Г. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The results of study of ecsiccatae of Herbarium Florae Rossica (1897–1907) of the historical herbarium of Uman College of Agriculture and Horticulture stored in the scientific herbarium of Uman National University of Horticulture have been presented. It has been established that the collection of the ecsiccatae includes 1911 herbarium samples which were obtained by exchange with the Botanical Department of the Saint-Petersburg society of researchers of nature. The authors identified quantitative composition of ecsiccatae of separate collectors of the Herbarium Florae Rossicaе and representation of their herbarium collections in other herbaria in Ukraine. In the 3rd issue of the Herbarium Florae Rossicae there has been revealed the presence of еcsiccatae, which were collected by students of Uman College of Agriculture and Horticulture in 1899.